The association of periodontal diseases with metabolic syndrome and obesity. Issue 1 (8th May 2020) - Jepsen, Søren; Suvan, Jean; Deschner, James
Abstract: Periodontitis is a multifactorial chronic inflammatory disease associated with dysbiotic plaque biofilms and characterized by progressive destruction of the tooth‐supporting apparatus. Globally, it is estimated that 740 million people are affected by its severe form. Periodontitis has been suggested to be linked to obesity and metabolic syndrome. Obesity, defined as excessive fat accumulation, is a complex multifactorial chronic inflammatory disease, with a high and increasing prevalence. Metabolic syndrome is defined as a cluster of obesity, dyslipidemia, hypertension, and dysglycemia. Obesity, metabolic syndrome and periodontitis are among the most common non‐communicable diseases and a large body of evidence from epidemiologic studies supports the association between these conditions. Extensive research has established plausible mechanisms to explain how these conditions can negatively impact each other, pointing to a bidirectional adverse relationship. At present there is only limited evidence available from a few intervention studies. Nevertheless, the global burden of periodontitis combined with the obesity epidemic has important clinical and public health implications for the dental team. In accordance with the common risk factor approach for tackling non‐communicable diseases, it has been proposed that oral healthcare professionals have an important role in the promotion of periodontal health and general well‐being through facilitation of healthy lifestyle behaviours.